Antimicrobial activity of novel 5-benzylidene-3-(3-phenylallylideneamino)imidazolidine-2,4-dione derivatives causing clinical pathogens: Synthesis and molecular docking studies - Daoud Ali; Saud Alarifi; Sathish Kumar Chidambaram; Surendra Kumar Radhakrishnan; Idhayadhulla Akbar (Elsevier, 2020)
Background: This work is development of new hydantoin molecules as treatment of potential antibacterial and antifungal activity against clinical pathogens causing infectious disease. Synthesized compounds were evaluated in molecular docking studies, the most effective compound is used to dock against the targets of 1U1Z, and 1AI9 kinases, to evaluate its binding affinity, hoping to rationalize and obtain potent of antibacterial, antifungal agents. Material and method: The FTIR, 1H & 13C NMR, and mass spectra were used to conform new molecules and their evaluation of antimicrobial activity. Gram-negative bacteria of Pseudomonas aeruginosa (ATCC-27853), Klebsiella pneumoniae (recultured) and Escherichia coli (ATCC-25922), and gram-positive bacteria of Enterococcus faecalis (recultured) and Staphylococcus aureus (ATCC-25923) were evaluated for all compounds. The in vitro antifungal activity was evaluated against Cryptococcus neoformans (recultured), Candida albicans (recultured), Aspergillus niger, Microsporum audouinii (recultured) and Aspergillus fumigatus (recultured) for all synthesized compounds. Result: Antibacterial screening, we identified highly active antimicrobial agents for this study for example; gram-negative bacterial screening of 3g was highly (MIC: 0.25 μg/mL) active in contradiction of P. aeruginosa, whereas bacterial screening of 3e and 3h were more active (MIC: 2 μg/mL) in contradiction of K. pneumoniae and also 3g was more (MIC: 2 μg/mL) active in contradiction of E. faecalis than standard ciprofloxacin. Antifungal activity, the 3b was more active (MIC: 0.25 μg/mL) against C. albicance, 3g (MIC: 2 μg/mL) and 3h (MIC: 4 μg/mL) were more potential of A. funigatus, and the compound 3c was highly (MIC: 4 μg/mL) active on M. audouinii than clotrimazole. Molecular docking studies also supported the new finding of potent antimicrobial agents, the compound 3g, 3b, and controls Ciprofloxacin, Clotrimazole were checked again proteins 1U1Z and 1AI9 by Autodock Vina program. The compound 3g was highest binding affinity (−8.4 kcal/mol) than ciprofloxacin (−8.2 kcal/mol) in 1U1Z protein and the compound 3b was highest binding affinity (−8.8 kcal/mol) than clotrimazole (−6.8 kcal/mol) in 1AI9 protein respectively. Conclusion: A novel set of imidazolidine-2,4-dione compounds 3a-h have synthesized and characterized successfully. The screening of antimicrobial activity shows that all compounds possess antimicrobial activities. In addition, the objective of the study was succeeded with a few of the promising molecules, which are proving to be a potential treatment of bacterial infection candidates.